Efficient separation of photoexcited carriers in a g-C3N4-decorated WO3 nanowire array heterojunction as the cathode of a rechargeable Li–O2 battery. Issue 36 (3rd September 2020) - Xue, Hairong; Wang, Tao; Feng, Yaya; Gong, Hao; Fan, Xiaoli; Gao, Bin; Kong, Yulong; Jiang, Cheng; Zhang, Songtao; Huang, Xianli; He, Jianping
Abstract : The efficient separation of photoexcited carriers within the g-C3 N4 -decorated WO3 nanowire array distinctly reduces the charging voltage and enhances the cycle performance of the photo-involved Li–O2 battery. Abstract : Utilization of solar energy is very important for alleviating the global energy crisis; however, solar-to-electric energy conversion in a compact battery is a great challenge. High charging overpotential of conventional aprotic Li–O2 batteries still restricts their practical application. Herein, we propose a photo-involved rechargeable Li–O2 battery to not only realize direct solar-to-electric energy conversion/storage but also address the overpotential issue. In this photo-involved battery system, the g-C3 N4 -decorated WO3 nanowire array (WO3 @g-C3 N4 NWA) heterojunction semiconductor is used as both the photoelectrode and oxygen electrode. Upon charging under visible-light irradiation, the photoexcited holes and electrons are in situ generated on the WO3 @g-C3 N4 NWA heterojunction cathode. The fabrication of the heterojunction can distinctly reduce the recombination rate between electrons and holes, while photon-generated carriers are effectively and quickly separated and then migrate under a large current density. The discharge product (Li2 O2 ) can be oxidized to O2 and Li + with a reduced charging voltage (3.69 V) by the abundant photoexcited holes, leading to high energy efficiency, good cycling stability and excellent rate capability. This newly photo-involved reaction scheme could open new avenues toward the design of advanced solar-to-electric energy conversion and storage systems.